Socialization and Education on Mass Production of Liquid Organic Fertilizer with the Addition of Local Microorganism Suspension (MOL) of Bacillus cereus Strain NIGR in Pantai Cermin Village, Tanjung Pura District, Langkat Regency - Nasution, Lita; Cemda, Abdul Rahman (Journal of Community Research and Service, 2022)
In order to succeed in the development of agricultural sector in accordance with the Regulation of the Minister of Agriculture Number 67/Permentan/SM.050/12/2016 concerning Farmer Institutional Development, it is necessary to provide community service in the agricultural sector and plant cultivation as efforts to strengthen food self-sufficiency, especially during the Covid 19 pandemic. For this reason, we need to carry out community service activities for the production of liquid organic fertilizer using microorganism Bacillus cereus in Pantai Cermin Village, Tanjung Pura District. As we know Pantai Cermin Village, Tanjung Pura District, Langkat which about is 63.6 Km from Medan. In general, the majority of farmers own rice and corn areas and are members of the Gemah Ripah farmer group consisting of 30 farmers. From the results of dedication program, there are around 3000 hectares of rice and corn fields that have become a rice barn for the last 15 years, especially in Langkat Regency. Based on the results of the survey and partner interviews, several priority problems were obtained, including: a. There was a decrease in the selling price of corn in Langkat by Rp. 1,900,-/Kg from the selling price of corn in 2019 of Rp. 4,900,-/Kg to Rp. 3,000,-/Kg currently in Langkat; b. Rice farmers experienced a decrease in purchasing power of chemical compost during the Pandemic, because the price of solid organic compost from the Probiodek brand that functions as a decomposer of organic matter rose to Rp. 40,000,-/Kg; c. Farmers experienced a decline in purchasing power of chemical insecticides on the market; d. Farmers in Langkat currently do not have a knapsacksprayer and they only use 2 units of knapsacksprayer from government assistance to spray plant pests & diseases and this tool is used interchangeably for all farmer groups; e. Farming management is carried out in a simple and conventional way, namely using local F1 seeds (yield) from the previous corn harvest); f. Rice harvesting as well as shelling corn use a simple method of rice mill machine. In order to develop the potential of rice and corn barns, it is necessary to strengthen the independence of farmers through community dedication program (PKM) training in the production of liquid organic fertilizer using microorganism Bacillus cereus from Ristekdikti. The focus is to develop production of liquid organic fertilizer as an alternative to chemical fertilizers and chemical insecticides. The use of microorganisms Bacillus cereus is especially useful for facilitating the decomposition of organic matter in liquid fertilizer solutions so that it is more easily absorbed by plants as fertilizer and insecticide, as well as assisting and motivating partners to continuously continue producing liquid organic fertilizers because it saves costs in purchasing chemical fertilizers and pesticides in the future so as to create economic independence for partners. This will certainly improve the economy of farmer group partners so that life can be more prosperous. All of these activities aim to foster independence in partners when the program ends. It is hoped that food self-sufficiency can be realized that is free from residues of chemical fertilizers and insecticides so that environmentally sustainable agriculture can be realized.